“Determinación del nivel organizacional de micro y pequeñas empresas de Quito, basado en un sistema integrado de gestión, 2013”. - Pacheco Lafuente, Esteban Alejandro (2014)
This research seeks to diagnose compliance with the requirements of a Integrated Management in a sample of 401 micro and small enterprises in the system Quito, in order to determine the organizational level and determine whether management aspects analyzed, can be considered as a factor that is influencing the increase in the detected output gap between companies different size in the country. The verification of compliance with the Integrated Management System, was conducted by performing a survey whose questions were based on the proposed requirements in the technical standard Ecuadorian NTE INEN 2537: 2010, which provides the requirements for a system Integrated Management, integrating aspects of business management, management resources, sales management, environmental and security management, and management of operations.